Is International Trade Causing a Bigger State? - Blaščík, Adam; Špecián, Petr; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
My thesis examines a paradoxical relationship between the openness of a country to the international trade and the size of its government. My hypothesis is that the openness causes growth of the government sector. Panel of five middle European countries is used for empirical verification of the hypothesis. I use the sum of import and export over GDP as a suitable proxy for openness of a country and total government revenue over GDP as a proxy for scope of a government. Using the random effects estimator, I found the negative effect of openness on the government size, but I failed to find this effect significant or robust. Hence, I discuss alternative explanations.
Vedoucí práce: Petr Špecián
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses